Aqueous core colloidosomes with a metal shell. (April 2016) - Sun, Qian; Routh, Alexander F.
Graphical abstract: Aqueous core microcapsules surrounded by an impermeable silver shell. Highlights: Facile method of production of aqueous core colloidosomes with metal shell. Self-assembly of capsules from emulsion precursor. Reduction of metal as final step. Abstract: Colloidosomes can be used in a wide variety of industries, such as food, bioreactors and medicine. We report for the first time, aqueous core colloidosomes with a gold or silver shell. The diameter of the water core is between 0.7 μm and 2 μm. The formation of gold coated colloidosomes was achieved by using sodium citrate (Na3 Citrate) in the core and gold chloride (HAuCl4 ) in the wash solution. The gold shell colloidosomes are covered with spherical gold particles. Silver coated colloidosomes can be prepared by usingl -Ascorbic acid in the core and silver nitrate (AgNO3 ) in the wash solution. Various processing parameters result in different shell morphologies. The silver shell can seal the core of the microcapsule, and the encapsulated material can be released by the addition of nitric acid.